2019
DOI: 10.3390/su11123244
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Predictors of Food Waste Behavior in Denmark and Spain

Abstract: Food waste generated at the household level represents about half of the total food waste in high-income countries, making consumers a target for food waste reduction strategies. To successfully reduce consumer food waste, it is necessary to have an understanding of factors influencing food waste behaviors (FWB). The objective of this study was to investigate socio-demographic predictors of FWB among consumers in two European countries: Denmark and Spain. Based on a survey involving 1518 Danish and 1511 Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 37 publications
2
32
3
2
Order By: Relevance
“…Previous studies have shown similar trends in food waste according to food purchaser sex. For example, in a study conducted in Denmark, it was found that male sex was associated with more food waste [36]. A study that explored consumer food waste among Romanians according to gender revealed that women tended to be more concerned about the negative impacts of food waste than men [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown similar trends in food waste according to food purchaser sex. For example, in a study conducted in Denmark, it was found that male sex was associated with more food waste [36]. A study that explored consumer food waste among Romanians according to gender revealed that women tended to be more concerned about the negative impacts of food waste than men [37].…”
Section: Discussionmentioning
confidence: 99%
“…This method is used to quantify the separate and cumulative effect of influencing variables on a target variable. It has recently been applied in other food waste and sustainability-related studies (Hameed et al 2019 ; Grasso et al 2019 ). Two types of SEM modeling are used widely: the covariance-based (CB) and the variance-based partial least square (PLS) method.…”
Section: Methodsmentioning
confidence: 99%
“…Rising global population is leading to increasing food production and consumption, eventually leading to growing food wastage [1][2][3]. These food wastes affect public health as well as the environment because they are disposed of by landfilling or incineration [4,5].…”
Section: Introductionmentioning
confidence: 99%